The Greenwood encyclopedia of Asian American literature - Huang, Guiyou 1961-; Gale Group (Westport, Connecticut Greenwood Press, 2009)
Contains entries on topics in Asian American literature, including writers, special topics, events, and terms. Covers literature by North American writers of Asian descent from the late 1890s to 2007, within a variety of contexts.
v. 1. A-G -- v. 2. H-M -- v. 3. N-Z.
Electronic reproduction.
Keywords: American literature -- Asian American authors -- Encyclopedias; American literature -- Asian American authors -- Bio-bibliography -- Dictionaries; Asian American authors -- Biography -- Dictionaries; Asian Americans -- Intellectual life -- Encyclopedias; Asian Americans in literature -- Encyclopedias; Electronic books